Characterizing forearm muscle activity in university-aged males during dynamic radial-ulnar deviation of the wrist using a wrist robot. (17th July 2020) - Forman, Davis A.; Forman, Garrick N.; Avila-Mireles, Edwin J.; Mugnosso, Maddalena; Zenzeri, Jacopo; Murphy, Bernadette; Holmes, Michael W.R.
Abstract: Functioning as wrist stabilizers, the wrist extensor muscles exhibit higher levels of muscle activity than the flexors in most distal upper-limb tasks. However, this finding has been derived mostly from isometric or wrist flexion-extension protocols, with little consideration for wrist dynamics or radial-ulnar wrist deviations. The purpose of this study was to assess forearm muscle activity during the execution of dynamic wrist radial-ulnar deviation in various forearm orientations (pronation/supination). In 12 healthy university-aged males, surface electromyography (EMG) was recorded from eight muscles of the dominant arm: flexor carpi radialis (FCR), flexor carpi ulnaris (FCU), flexor digitorum superficialis (FDS), extensor carpi radialis (ECR), extensor carpi ulnaris (ECU), extensor digitorum (ED), biceps brachii (BB) and triceps brachii (TB). While grasping a handle, participants performed dynamic radial-ulnar deviation using a three-degrees-of-freedom wrist manipulandum. The robotic device applied torque to the handle, in either a radial or ulnar direction, and in one of three forearm postures (30° supinated/neutral/30° pronated). Results indicated that forearm posture influenced the muscles acting upon the hand (FDS/ED), whereas movement phase (concentric-eccentric) and torque direction influenced nearly every muscle. The ECR demonstrated the greatest task-dependency of all forearm muscles, which is possibly reflective of forearm muscle lines of action. Co-contraction ratios were much higher in radial trials than ulnar (Radial: 1.20 ± 0.78, Ulnar: 0.28 ± 0.18, P < 0.05), suggesting greater FCU and ECU contribution to wrist joint stability in radial-ulnar movement. These findings highlight a greater complexity of wrist extensor function than has previously been reported in isometric work.